The role of ADAM10 in the prediction of neoadjuvant chemoradiotherapy response in patients with locally advanced rectal cancer - Isaković, Anđelka M.; Dragičević, Sandra; Ugrin, Milena; Miladinov, Marko; Barišić, Goran; Nikolić, Aleksandra; Misirlić-Denčić, Sonja (Archives of Biological Sciences, 2025)
Paper description: Protein ADAM10 is implicated in colorectal cancer development. This study evaluates ADAM10 expression and serum levels in locally advanced rectal cancer (LARC) patients undergoing neoadjuvant chemoradiotherapy (nCRT). Pre-nCRT samples from 23 LARC patients were analyzed for ADAM10 expression using RT-qPCR and serum concentrations by ELISA, with correlation to nCRT response. Tumor tissue had significantly higher ADAM10 expression (83% of patients) than healthy tissue. Serum levels varied widely and did not correlate with tissue expression or nCRT response. ADAM10’s involvement in rectal cancer biology is confirmed, warranting further research on its substrates and signaling pathways. Abstract: Protease ADAM10, a member of the A disintegrin and metalloproteinase protein family, plays a role in cytokine/growth factor release, the shedding of receptor molecules from the membrane, and intracellular signaling. ADAM10 is implicated in colorectal cancer development and progression and has been identified as a potential predictive biomarker in this disease. This study evaluates ADAM10 expression in tumor and non-tumor tissue and ADAM10 serum concentrations in patients with locally advanced rectal cancer (LARC) treated with neoadjuvant chemoradiotherapy (nCRT). The study included samples taken before nCRT from 23 histopathologically confirmed LARC patients. Expression of ADAM10 was assessed using RT-qPCR, while ELISA measured ADAM10 concentrations in the serum, and the correlation of the results with nCRT response was evaluated. We found statistically significantly higher expression of ADAM10 in tumor tissue compared to healthy tissue in 83% of LARC patients. Serum concentrations of ADAM10 varied widely (66.6-1119.1 pg/mL) and did not correlate with tissue expression levels. Neither the tissue expression level nor ADAM10 serum concentrations predicted the response to nCRT. Our results confirm the involvement of ADAM10 in rectal cancer initiation and warrant further research on ADAM10 substrates, signaling pathways involved in its activity, and its potential as a therapeutic target.